Genome-wide identification and drought stress-induced expression analysis of the NHX gene family in potato - Yihong, Ji; Zhen, Liu; Chang, Liu; Ziying, Shao; Ning, Zhang; Meiqing, Suo; Yuhui, Liu; Lei, Wang (Frontiers in Genetics, 2024)
NHX proteins are transmembrane antiporters belonging to the cation/proton antiporter gene family, with a conserved Na+ (K+)/H+ exchange (PF00999) protein domain. NHXs play a prominent role in plant growth, development, and defense. However, the role of NHX gene family in potato (Solanum tuberosum L.) is yet to be known. In this study, we conducted a genome-wide analysis of the potato NHX gene family. A total of 25 StNHX family members were identified to be unevenly distributed on 10 chromosomes. The proteins ranged in length from 252 to 1,153 amino acids, with molecular masses ranging from 27516.32 to 127860.87 kD, and isoelectric points (pI) ranging from 4.96 to 9.3. Analyses of gene structures and conserved motifs indicated that StNHX genes in the same phylogenetic cluster are conserved. Phylogenetic analysis divided the StNHX genes into three subfamilies (Classes I, II, and III). Synteny analysis indicated that StNHX gene family Class III of NHX and all Arabidopsis thaliana NHXs shared a close evolutionary relationship. Analysis of cis-acting elements in the upstream 1,500 bp promoter region of potato NHX genes showed that these genes could be regulated by light, stress, and hormones such as abscisic acid and gibberellic acid. Protein-protein interaction network analysis indicated that StNHX proteins may participate in the regulation of potato growth and stress response. Besides, To determine a potential role of these genes in tissue development and drought response, we analyzed the RNA-seq data of different DM potato tissues. The results showed that NHX genes exhibited distinct tissue-specific expression patterns. We further examined the expression patterns of StNHX in different tissues (leaves, roots, shoots, tubers, stolons, and flowers) during the flowering stage in ‘Jizhangshu NO.8.’ potato. The qRT-PCR results further confirmed the importance of StNHX genes in potato plant growth and development. We further analyzed the RNA-seq data (DM potato) under different abiotic stresses (salt, drought, and heat), and found that the expression of StNHX genes was induced under abiotic stress. qRT-PCR analysis of shoots and roots of ‘Jizhangshu NO.8.’ potato treated for 0, 6, 12, and 24 h with 15% PEG6000 confirmed that the 25 StNHX genes are involved in the response to drought stress in potato. The results of this study may be useful for selecting appropriate candidate genes for the breeding of new drought-tolerant potato varieties. Furthermore, this study lays a foundation for prospective analysis of StNHX gene functions.